Empirical correlations for pressure drop across A chromatographic bed packed with A compressible packing - Abdul Wahab Mohammad, (1993)
Experiments were done to obtain a correlation between pressure drop across a chromatographic bed packed with a compressible packing, Sephadex G100, and other measurable parameters such as flowrate, column length and diameter, particle size, and permeability. The pressure drop across the bed is obtained by subtracting the extracolumn pressure drop from the operating pressure drop. It was found that the pressure drop increased nonlinearly as the flowrate increased. There is a critical flowrate after which the pressure drop increases infinitely. The pressure drop was also found to be dependent on the column diameter within the range tested. The data were fitted well with an equation similar to the Blake-Kozeny equation but with an exponential term and a critical factor included